Location, Clinical Presentation, Diagnostic Algorithm and Open vs. Arthroscopic Surgery of Knee Synovial Haemangioma: A Report of Four Cases and a Literature Review - Hernández-Hermoso, José A.; Moranas-Barrero, José; García-Oltra, Ester; Collado-Saenz, Fernando; López-Marne, Sylvia (Frontiers in Surgery, 2021)
Objective. The aim was to report 4 patients with intra-articular knee synovial haemangioma (KSH) and to perform a systematic review to describe the patient characteristics, patterns of tumour location, clinical presentation, usefulness of imaging examinations, pros and cons of arthroscopic versus open resection, and follow-up in the literature. Design: From 1996 to 2016, 4 patients with KSH were retrospectively reviewed. A literature search was conducted in PubMed from 2000/01 to 2020/06 using the search terms “synovial haemangioma” and “knee”. Fifty full-text articles that included a total of 92 patients were included for further discussion. Results: Four adults (20-40 years) were diagnosed with KSH. Three lesions located in the suprapatellar pouch, two eroding the patella and one the supratrochlear bone, and one in the posterior compartment. Persistent anterior knee pain was the main complain. MRI revealed a benign tumour mass in all cases except one. Open excisional biopsy and regional synovectomy were performed in three patients, and by arthroscopy of the posterior compartment in the fourth. Histological type was arteriovenous in three cases and capillary in one. A pain-free knee without recurrence was achieve in all cases except one, which was successfully reoperated. Average follow-up time was 3.5 years. A literature review showed that KSH appears most frequently in children and teenagers (64.6%) and does not differ by gender. The suprapatellar and patella-femoral joint compartment was the most frequent location (47.9%). The bony tissue of the knee was rarely affected (13.5%). Pain, swelling and haemarthrosis were frequently reported (88.2, 66.7 and 47.1%). MRI was the most commonly used imaging test (98%). Treatment consisted of regional synovectomy by open surgery or arthroscopy in 66.7 and 15.6% of cases, respectively. Conclusions: KSH should be considered in the differential diagnosis of adult patients with chronic low-intensity knee pain. MRI is the most useful exam because it establishes the location, extent and benign characteristics of the tumour. Definitive diagnosis requires histological examination. We believe excisional biopsy and regional synovectomy by arthroscopy should be the treatments of choice for intra-articular tumours, but we recommend open surgery when the lesion extends to the tendons, muscle or bone.